Estratégias de marketing digital para promoção do curso de ciência da computação da unioeste-foz do iguaçu - Mafra, André Luis Gambetta (2023)
In a time when technology allows people to be increasingly connected through devices and social media, Higher Education Institutions - HEI need to reconsider how to work their marketing strategies to explore these spaces, since the use of traditional concepts is no longer sufficient. With the technological development observed in past years, a large plethora of possibilities have emerged for the HEI to connect with their communities, with their alumni, current and future students digitally. Therefore, the digital marketing concepts and tools need to be assimilated and adopted, to guarantee the visibility of HEI in the educational market, especially public institutions that, in many cases, don´t have the financial resources and dedicated staff for this task. The segment, specifically in some undergraduate courses, can be highly competitive. At the same time, many national and international institutions, public and private are disputing the preference of new students. Thus, this project has the intent of establishing digital marketing strategies for the Computer Science course of the West Paraná State University – Foz do Iguaçu Campus, in order to make it known to the community as a high-quality course, with excellent opportunities in the work force. To achieve this, a brand proposition was elaborated, followed by a survey about semantical differentials applied to current students to identify if the visual identity developed in this project was in accordance with their expectations. Furthermore, the target audience characteristics were outlined, which consequently allowed for the development of more efficient digital marketing strategies for the Computer Science course. The expectation is that these bring results that add value to the course in the perspective of its students, professionals, and community in general.